Thrombin inhibits nuclear factor κB and RhoA pathways in cytokine-stimulated vascular endothelial cells when EPCR is occupied by protein C - Bae, Jong-Sup; Rezaie, Alireza R. (Thrombosis and Haemostasis, 2009)
The occupancy of endothelial protein C receptor (EPCR) by protein C switches the protease activated receptor 1 (PAR-1)-dependent signalling specificity of thrombin from a permeability enhancing to a barrier protective response in vascular endothelial cells. In this study, the modulatory effects of thrombin and thrombin receptor agonist peptides (TRAP) on tumour necrosis factor (TNF)-α-stimulated HUVECs in the absence and presence of the catalytically inactive protein C-S195A were evaluated by monitoring the expression of cell surface adhesion molecules (VCAM-1, ICAM-1 and E-selectin), adhesion of freshly isolated neutrophils to cytokine-stimulated endothelial cells, regulation of the Rho family of small GTPases and the activation of nuclear factor-κB (NF-κB) pathway. The analysis of results indicate that both thrombin and TRAP initiate proinflammatory responses in endothelial cells, thus neither PAR-1 agonist in-fluenced the proinflammatory effects of TNF-α in the absence of the protein C mutant. Interestingly, however, the occupancy of EPCR by the protein C mutant switched the PAR-1-dependent signaling specificity of thrombin, thus leading to thrombin inhibition of the expression of all three adhesion molecules as well as the binding of neutrophils to TNF-α-activated endothelial cells. Furthermore, similar to activated protein C, both thrombin and TRAP activated Rac1 and inhibited the activation of RhoA and NF-κB pathways in response to TNF-α in cells pre-treated with protein C-S195A. Based on these results we conclude that when EPCR is ligated by protein C, the cleavage of PAR-1 by thrombin initiates antiinflammatory responses, thus leading to activation of Rac1 and inhibition of RhoA and NF-κB signalling cascades in vascular endothelial cells.
Keywords: Thrombin; EPCR; PAR-1; protein C; cell adhesion; NF-κB; Rho